2015
DOI: 10.1007/s11255-015-0924-1
|View full text |Cite
|
Sign up to set email alerts
|

Intradetrusor injection of adult muscle-derived cells for the treatment of underactive bladder: pilot study

Abstract: We conducted the first-regenerative medicine cellular therapy for underactive bladder (UAB) in an FDA-approved, compassionate-use IND trial to evaluate treatment safety and potential clinical efficacy of autologous muscle-derived stem cells (AMDC) on a patient with UAB. No study-related adverse events or side effects were reported. In the 1-year follow-up period, the subject denied any gross hematuria, urgency, frequency or infection. A reduction in maximum cystometric capacity from 844 to 663 mL was observed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 5 publications
2
27
0
Order By: Relevance
“…In this study we showed that the ratio of structural markers smoothelin to osteopontin mRNA and not aSMA mRNA, accurately describe the structural changes and loss of in‐vitro contractile properties in the bladder of neurogenic UAB rats. The smoothelin/osteopontin mRNA ratio could serve as a tool to evaluate the effect of new therapies for UAB …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we showed that the ratio of structural markers smoothelin to osteopontin mRNA and not aSMA mRNA, accurately describe the structural changes and loss of in‐vitro contractile properties in the bladder of neurogenic UAB rats. The smoothelin/osteopontin mRNA ratio could serve as a tool to evaluate the effect of new therapies for UAB …”
Section: Resultsmentioning
confidence: 99%
“…The smoothelin/osteopontin mRNA ratio could serve as a tool to evaluate the effect of new therapies for UAB. 31…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Levanovich et al reported a pilot study on intradetrusor injection of adult muscle-derived cells (AMDC) in a human DUA patient [63], a 79-year-old man who had twice undergone transurethral resection of the prostate and suffered from recurrent urinary retention despite the administration of alpha blockers and bethanechol. The patient was on clean intermittent catheterization 4 to 6 times per day but had repeated episodes of gross hematuria and febrile urinary tract infections.…”
Section: Detrusor Underactivity (Dua)mentioning
confidence: 99%
“…Both overactive bladder and underactive detrusor have reported to have improved outcomes in preclinical studies with local injections of adipose derived stem cells ( 14 ). While there have been case reports in human patients the results have been not been completely successful ( 15 ). Bladder augmentation using a tissue engineered bladder has been described in many trials and perhaps is most likely to be adopted clinically ( 16 ).…”
Section: Bladder Augmentation Detrusor Underactivity and Neurogenic mentioning
confidence: 99%